2000
DOI: 10.1093/ajcn/71.2.500
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in energy expenditure and aerobic fitness in premenopausal women

Abstract: African American women had lower aerobic fitness than did white women, independent of differences in lean tissue or AEE. Diminished racial differences in SEE, REE, and TEE after adjustment for trunk lean tissue suggest that low EE in African American women is mediated by low volumes of metabolically active organ mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 27 publications
6
72
1
Order By: Relevance
“…However, these ethnic differences were largely attributed to differences in PAEE, and not as a result of lower REE, as previously reported in studies from the United States (Albu et al, 1997;Foster et al, 1997;Carpenter et al, 1998;Hunter et al, 2000;Weinsier et al, 2000Weinsier et al, , 2002Lovejoy et al, 2001;Sharp et al, 2002). In the present study, total PAEE was on average 25% lower in the black as compared to white women, largely due to between-group differences in the weight-bearing stepping exercise, where white obese women accumulated a significantly greater PAEE (11%) than black women.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, these ethnic differences were largely attributed to differences in PAEE, and not as a result of lower REE, as previously reported in studies from the United States (Albu et al, 1997;Foster et al, 1997;Carpenter et al, 1998;Hunter et al, 2000;Weinsier et al, 2000Weinsier et al, , 2002Lovejoy et al, 2001;Sharp et al, 2002). In the present study, total PAEE was on average 25% lower in the black as compared to white women, largely due to between-group differences in the weight-bearing stepping exercise, where white obese women accumulated a significantly greater PAEE (11%) than black women.…”
Section: Discussionsupporting
confidence: 81%
“…Studies (Albu et al, 1997;Carpenter et al, 1998;Hunter et al, 2000;Lovejoy et al, 2001;Sharp et al, 2002;Weinsier et al, 2002) have reported lower resting energy expenditure (REE) in obese and reduced obese African American (AA) women compared to their white counterparts (Foster et al, 1997;Weinsier et al, 2000). This difference in REE persists even after adjusting for differences in fat-free mass (FFM) (Foster et al, 1999), and is thought to contribute to the higher obesity prevalence found in the AA compared to the white population.…”
Section: Introductionmentioning
confidence: 99%
“…The results have been consistent across a number of studies, in children, 12 adolescent girls, 13 young overweight women, 31 Black male middle distance runners, 14 and premenopausal women. 15 Bassett and Howley 32 have outlined four factors that limit maximum oxygen uptake: (1) pulmonary diffusing capacity; (2) maximum cardiac output; (3) oxygen carrying capacity of the blood; and (4) skeletal muscle characteristics. Pivarnik et al 13 have previously shown that venous hemoglobin levels are lower in Black than White adolescent girls, and we 33 have shown the same difference in Black vs White premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that differences in VO 2 max between Black and White women persist even after adjusting for differences in free-living physical activity. 15 The implication is that differences in aerobic capacity between Black and White subjects are independent of differences in physical activity. If this is the case, it becomes more likely that racial differences in physical activity are mediated by differences in aerobic fitness and the difficulty of being physically active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation